Analysis of Firm Value Using Financial Ratios and Board of Directors Characteristics Through the Tobin's Q Method - Anindia Hadiyati Utami; Erna Listyaningsih; Hiro Sejati (Yayasan Multidimensi Kreatif, 2026)
This study aims to analyze the effect of Return on Assets (ROA), Firm Size, Leverage, Board Size, and Board Independence on firm value, as proxied by Tobin's Q, in energy sector companies listed on the Indonesia Stock Exchange during the 2022–2024 period. The research sample was selected using a purposive sampling method and included energy sector companies that consistently published complete financial reports during the study period. The data used were secondary, while the analytical technique applied included panel data regression, with the best model selected using the Chow, Hausman, and Lagrange Multiplier tests. The results showed that Return on Assets had a positive and significant effect on firm value, Firm Size had a negative and significant effect on firm value, while Leverage, Board Size, and Board Independence had no significant effect on firm value. Simultaneously, all independent variables significantly influenced firm value, indicating that a combination of financial performance factors and corporate governance characteristics play a role in determining the value of energy sector companies.